Effects of urban life on the gut microbiota and the susceptibility to avian malaria infection in a population of the house sparrow Passer domesticus - Daliborka Stanković; Hugo J. Eira Pereira; Marko Raković; Stefan Skorić; Nayden Chakarov (Journal of Avian Biology, 2025)
Life in urban areas may alter the gut microbiota and host physiology, leading to a higher susceptibility to pathogens. In contrast, specific members of the gut microbiota community have been shown to mitigate the intensity of malaria infection. House sparrows, living in close proximity to humans, are exposed to a unique environment with human‐shaped diets emerging as a particularly influential factor. In addition, sparrows host a significant number of avian haemosporidian and other blood parasites. We examined how the gut bacterial community of house sparrows varied across two close urban sites in the city of Belgrade and the potential impact of blood parasite infection on the gut microbiota. Our results show that diversity and composition of the gut microbiota were only influenced by the sampling location, likely due to variations in food resources, particularly the availability of bird feed at one of the sites (a zoo). In summary, our results suggest the local microbial adaptations to differing levels of urbanisation habitats, in this case most likely driven by artificial alterations in food resources, but not reaching to effects on the blood parasite fauna.